Modelling ultrafine particle number concentrations at address resolution in Denmark from 1979-2018 – Part 1: Regional and urban scale modelling and evaluation. (1st November 2021) - Frohn, Lise Marie; Ketzel, Matthias; Christensen, Jesper Heile; Brandt, Jørgen; Im, Ulas; Massling, Andreas; Andersen, Christopher; Plejdrup, Marlene Schmidt; Nielsen, Ole-Kenneth; Gon, Hugo Denier van der; Manders-Groot, Astrid; Raaschou-Nielsen, Ole
Abstract: The integrated model system DEHM/UBM/AirGIS, developed at Aarhus University, Department of Environmental Science, has been extended with the dynamic aerosol module M7 to account for particle number concentrations of particles with diameters below 1 μm in the atmosphere. The aim of this development is to quantify the spatial and temporal distribution of particle number concentration across Denmark and evaluate the results with available measurements. This article presents model results for particle number concentrations from the regional scale model DEHM and the urban scale model UBM, for comparison with measurements of particle number concentrations from European and Danish measurement stations. The deterministic modelling of particle number concentration has been vitiated by the lack of consistency between emission inventories, and the evaluation of the models is challenged by the lack of consistent long-term measurements data. The performance evaluation of the DEHM and UBM models shows that both models overestimate the level of the particle number concentrations at all stations, however, the results for the correlation coefficients are 0.86 for DEHM and in the range from 0.86 to 0.87, for UBM, for annual mean particle number concentrations at Danish measurement stations. We conclude that the inclusion of particle number concentration in DEHM and UBM shows some capability of reproducing observed patterns, when comparing the results of the models with available measurements, but that there is also room for improvement, especially with respect to the emission inventories and preprocessing of emissions and to the treatment of volatile organic compounds based on natural emissions during summer time.